Socio-Economic and Livelihood Status of Inland Fisher Communities in Five Selected Reservoirs of Kilinochchi District, Northern Province, Sri Lanka - Diriyan, S.; Thatchaneshkanth, S.; Sankeethan, K. (University of Jaffna, 2021)
Kilinochchi district is well known for its abundance of multi-purpose reservoirs used for agricultural activities and freshwater aquaculture. Despite their abundance, no study has been conducted for the crucial information required for the aquaculture development. Therefore, the current study focuses on the socio economic and livelihood status of fishermen which acts as the baseline information for future development. Fishing communities were selected from the five major reservoirs, namely Akkarayan, Vannery, Murippu, Premanthanaru, and Iranaimadu in the Kilinochchi district using a structured questionnaire survey (184) to obtain general and fish production related information. The study revealed that the majority of fishermen (62.2–93.3%) were Hindus while Christians were recorded at the range between 6.7–37.8% were from five reservoirs. 31–60% of the fishermen belong to the age group between 35–45 years in all the reservoirs except Iranaimadu, however younger fishermen (25–35 years) community (26%) has been reported from Iranaimadu. About 83-100% of the fishermen from all reservoirs were married, obtained at least primary or secondary education, constructed fairly proper housing with sanitary facilities. Majority of the fishermen (39–85%) has engaged with this sector after the year, 2010 except the Vannery reservoir due to the civil conflict. In all reservoirs, 92.3–100% of fishermen has directly engaged with the inland fishery as their major livelihood. Further, gillnet (93.3–100%) is predominantly used for harvesting Indian carp and Tilapia and, production is up to 100 kg and less than 5 kg per attempt during high yield season (dry period) and off-season (rainy period) respectively. In Akkarayan, more than 86% of fishermen earn less than 10,000 LKR monthly while nearly 40,000 LKR per month is the income of 60 % of fishermen in Premanthanaru. Inland fish production shows relatively lower production due to the past civil war although inland fishery plays a major role in rural employment in Kilinochchi. Sustainable fishery management policies, effective stocking, technical, financial and, social support may improve the livelihood of the fishers by, ultimately increasing the overall inland fishery productivity in Kilinochchi District
Keywords: inland fishery; structured questionnaire; multi-purpose reservoirs